A Bibliometric Analysis of Trends in Various Treatment Modalities for Dental Fluorosis - B Pawar, Dr. Saurabhachandra; Lavekar, Dr. Pranoti; Pawar, Dr. Rasika; Deshpande, Dr. Utkarsha; Buddhikot, Dr. Chaitanya; G. Pardeshi, Dr. Dipti. (International Journal Of Drug Research And Dental Science, 2025)
Background: Dental fluorosis is a condition where enamel is hypoplastic due to increased fluoride ingestion. The affected teeth appear whitish opaque or discoloration which ranges from yellowish to grey concerning the severity of fluorosis leading to breakdown and aesthetic disturbances. This study highlights the need of minimally and non-invasive approaches for the treatment of dental fluorosis in young adults as an adjuvant for invasive procedures.Methodology: A comprehensive search and selection strategy was framed with appropriate Boolean operators to retrieve maximum and relevant results. For inclusion, the SCOPUS database, such as, in the subject area, dentistry was selected: free full-text articles were included, only abstracts were excluded, and articles only in the English language were included. All the included articles were imported as a. CSV file to VOSviewer 1.6.8 software (Centre for Science and Technology Studies, Leiden University, Leiden, Netherlands) for bibliometric analyses.Results: Among the search literature, review articles occupied the majority with 12.2% with the highest amount of documentation carried out by the United States with 6304 citations with the highest amount of literature published in Journals like Children, Clinical Dentistry Russia, International Journal of Dentistry and Oral Sciences, Clinical Oral Investigations and Scientific Reports.Conclusion: There is a significant difference in the efficacy of bleaching and microabrasion as there is no difference between bleaching and resin infiltration in the treatment of dental fluorosis.